Use of Polyamide (Nylon) Cable Ties for Vascular Ligation of Healthy Equine Jejunal Mesentery - Hurcombe, Samuel D.; Roessner, Holly A.; Klein, Chelsea E.; Engiles, Julie B.; Hopster, Klaus (Frontiers in Veterinary Science, 2021)
Jejunal vascular ligation is an essential step in performing jejunojejunostomy. Hand sewn ligation is typically used and can increase operative time with long sections of bowel to be removed. Nylon cable ties (NCT) have been used for vascular ligation in horses but are yet to be investigated for application on the mesenteric vasculature of the gastrointestinal tract. Our objective was to evaluate the efficacy and short-term safety of NCT jejunal mesenteric vessel ligation in healthy horses. Eight healthy adult horses underwent midline celiotomy. A segment of jejunal mesentery was identified (≥4 arcades). Briefly, three fenestrations (proximal, middle, distal) were made 5-10mm apart adjacent to the first and last vascular arcade to be ligated. Two sterilized NCT were passed to encircle the mesentery through the proximal and middle fenestrations, separated by intact mesentery. NCT were closed tightly and the vascular pedicle transected with Mayo scissors through the distal fenestration. Jejunojejunostomy was then performed and the mesentery sutured closed. The number of vascular arcades and time to ligate using NCT were recorded. At two weeks, horses underwent repeat celiotomy to assess the healing of the NCT ligation site and an equal number of vascular arcades were hand sewn double ligated using 2-0 Polyglactin 910 as a timed comparison. NCT mesenteric ligation was significantly faster than hand sewn methods (P<0.01). Effective hemostasis was achieved in all cases. There was no evidence of local infection or adhesions at 14 days post-operatively. Further investigation in the long-term effects in horses as well as horses with strangulating jejunal lesions are needed for clinical application.